Structural drivers and social protection: mechanisms of HIV risk and HIV prevention for South African adolescents - Cluver, L.; Orkin, F.; Meinck, F.; Boyes, Mark; Sherr, L. (BioMed Central Ltd., 2016)
Introduction: Social protection is high on the HIV-prevention agenda for youth in sub-Saharan Africa. However, questions remain: How do unconditional cash transfers work? What is the effect of augmenting cash provision with social care? And can ‘‘cash plus care’’ social protection reduce risks for adolescents most vulnerable to infection? This study tackles these questions by first identifying mediated pathways to adolescent HIV risks and then examining potential main and moderating effects of social protection in South Africa. Methods: This study was a prospective observational study of 3515 10-to-17-year-olds (56.7% female; 96.8% one-year retention). Within randomly selected census areas in four rural and urban districts in two South African provinces, all homes with a resident adolescent were sampled between 2009/2010 and 2011/2012. Measures included 1) potential structural drivers of HIV infection such as poverty and community violence; 2) HIV risk behaviours; 3) hypothesized psychosocial mediating factors; and 4) types of social protection involving cash and care. Using gender-disaggregated analyses, longitudinal mediation models were tested for potential main and moderating effects of social protection. Results: Structural drivers were associated with increased onset of adolescent HIV risk behaviour (pB0.001, B_0.06, SE_0.01), fully mediated by increased psychosocial problems. Both cash and care aspects of social protection were associated with reductions in HIV risk behaviour and psychosocial deprivations. In addition, cash social protection moderated risk pathways: for adolescent girls and boys experiencing more acute structural deprivation, social protection had the greatest associations with HIV risk prevention (e.g. moderation effects for girls: B= -0.08, p <0.002 between structural deprivation and psychosocial problems, and B= -0.07, p <0.001 between psychosocial problems and HIV risk behaviour). Conclusions: Adolescents with the greatest structural deprivation are at higher risk of HIV, but social protection has the greatest prevention effects for the most vulnerable. Social protection comprising unconditional cash plus care was associated with reduced risk pathways through moderation and main effects, respectively. Our findings suggest the importance of social protection within a combination package of HIV-prevention approaches.